Children's Moral Emotion Attribution in the Happy Victimizer Task: The Role of Response Format. Issue 1 (2nd January 2016) - Gummerum, Michaela; López-Pérez, Belén; Ambrona, Tamara; Rodríguez-Cano, Sonia; Dellaria, Giulia; Smith, Gary; Wilson, Ellie
ABSTRACT: Previous research in the happy victimizer tradition indicated that preschool and early elementary school children attribute positive emotions to the violator of a moral norm, whereas older children attribute negative (moral) emotions. Cognitive and motivational processes have been suggested to underlie this developmental shift. The current research investigated whether making the happy victimizer task less cognitively demanding by providing children with alternative response formats would increase their attribution of moral emotions and moral motivation. In Study 1, 93 British children aged 4–7 years old responded to the happy victimizer questions either in a normal condition (where they spontaneously pointed with a finger), a wait condition (where they had to wait before giving their answers), or an arrow condition (where they had to point with a paper arrow). In Study 2, 40 Spanish children aged 4 years old responded to the happy victimizer task either in a normal or a wait condition. In both studies, participants' attribution of moral emotions and moral motivation was significantly higher in the conditions with alternative response formats (wait, arrow) than in the normal condition. The role of cognitive abilities for emotion attribution in the happy victimizer task is discussed.